2007
DOI: 10.1111/j.1365-2044.2007.05003.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Levitan FPS Scope and the single‐use bougie for simulated difficult intubation in anaesthetised patients

Abstract: SummaryA randomised cross-over study was performed in 34 patients with no evidence of airway difficulties, following induction of general anaesthesia, to compare the efficacy of the Levitan FPS scope TM (LFPS) and the single-use bougie for tracheal intubation during simulated grade IIIa laryngoscopy. Success rates for intratracheal placement of the device, and the time required for insertion and tracheal intubation were recorded. Both devices were equally successful (31 ⁄ 34 for the LFPS vs 29 ⁄ 34 for the bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The manufacturer has recommended a variety of intubation techniques: as a stand‐alone device; its use with a Macintosh blade; or with a ‘chin‐lift’ technique. Although several such malleable fibre optic scopes have been available for some time [10], there is still a paucity of literature documenting their clinical efficacy in managing the difficult airway [11, 12]. Hence, we evaluated the use of the Shikani optical stylet as an alternative to the GlideScope videolaryngoscope in anaesthetised patients with cervical immobilisation simulating a difficult airway.…”
mentioning
confidence: 99%
“…The manufacturer has recommended a variety of intubation techniques: as a stand‐alone device; its use with a Macintosh blade; or with a ‘chin‐lift’ technique. Although several such malleable fibre optic scopes have been available for some time [10], there is still a paucity of literature documenting their clinical efficacy in managing the difficult airway [11, 12]. Hence, we evaluated the use of the Shikani optical stylet as an alternative to the GlideScope videolaryngoscope in anaesthetised patients with cervical immobilisation simulating a difficult airway.…”
mentioning
confidence: 99%
“…In previously published studies evaluating newer fibreoptic scopes, the laryngeal view was not graded or the mannequin or patients had a predetermined Cormack-Lehane grade. 2,10,11 With respect to safety, we found no difference in the frequency of trauma or complaints of sore throats between Data presented as mean difference and 95% confidence intervals (paired one-way analysis of variance). SBP = systolic blood pressure; HR = heart rate the LFS and Macintosh as the technique used for actual tracheal intubation.…”
Section: Discussionmentioning
confidence: 82%
“…These results support Greenland et al's previously reported findings published in a similar bougie vs LFS study. 2 These authors reported longer LFS insertion times, yet both techniques were equal in time to intubate and success at intubating the trachea in standardized simulated grade IIIa difficult airways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulating a difficult airway in patients for the purpose of clinical study is not a new concept, with several approaches described. Two commonly adopted methods include: undertaking direct laryngoscopy with a Macintosh laryngoscope blade, then reducing traction, allowing the epiglottis to fall posteriorly, thereby creating an obscured view of the vocal cords with an adjustable degree of difficulty ; and application of a rigid cervical collar, as favoured by Kleine‐Brueggeney et al, designed to create a physical restriction of neck flexion, head extension and mouth opening as might occur in a patient with cervical spine instability. Since there are advantages and disadvantages of both of these techniques (in terms of airway accessibility, practicality, reliability, reproducibility and generalisability), the choice of which technique to adopt is largely governed by the nature of the difficult airway intended and the type of airway device or technique under investigation.…”
Section: Patients Not Manikinsmentioning
confidence: 99%